2019
DOI: 10.2478/jvetres-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection with T. canis and T. leonina in farm mink (Neovison vison)

Abstract: Introduction: Farm mink (Neovison vison) can be naturally exposed to T. canis and T. leonina pathogens on the farm. If mink were hosts, it would imply some veterinary public health as well as animal welfare issues. For this reason, the aim of the study was to determine whether mink might be definitive or paratenic hosts of these parasites. Material and Methods: Four groups of mink were infected with both parasite species using larvated eggs or feed containing mouse tissue previously infected with the parasites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Serological methods offer a sensitive and relatively specific alternative to necropsies or digestion methods. The usefulness of both ELISA and Western blot was confirmed, for example, in T. canis and T. leonina diagnoses in experimentally infected paratenic hosts (Klockiewicz et al 2019a). No false-posi-tive/false-negative results were stated in this study.…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…Serological methods offer a sensitive and relatively specific alternative to necropsies or digestion methods. The usefulness of both ELISA and Western blot was confirmed, for example, in T. canis and T. leonina diagnoses in experimentally infected paratenic hosts (Klockiewicz et al 2019a). No false-posi-tive/false-negative results were stated in this study.…”
Section: Introductionsupporting
confidence: 69%
“…In this study, tissue larvae were found in experimentally infected farm American mink; histopathological examinations of parenchymal organs and striated muscles revealed lesions resembling those observed in other paratenic hosts due to toxocarosis (Klockiewicz et al 2019b). In addition, this infection was irrevocably confirmed by both ELISA and Western blot (Klockiewicz et al 2019a). Several up-to-date parasitological studies of American mink have been conducted in Belarus (Shimalov and Shimalov 2001a), Spain (Torres et al 2003), France (Torres et al 2008), andPoland (Kołodziej-Sobociń ska et al 2018), but neither adult Toxocara spp.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations